2006
DOI: 10.1002/bies.20436
|View full text |Cite
|
Sign up to set email alerts
|

The pea aphid, Acyrthosiphon pisum: an emerging genomic model system for ecological, developmental and evolutionary studies

Abstract: Aphids display an abundance of adaptations that are not easily studied in existing model systems. Here we review the biology of a new genomic model system, the pea aphid, Acyrthosiphon pisum. We then discuss several phenomena that are particularly accessible to study in the pea aphid: the developmental genetic basis of polyphenisms, aphid–bacterial symbioses, the genetics of adaptation and mechanisms of virus transmission. The pea aphid can be maintained in the laboratory and natural populations can be studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 79 publications
0
74
0
Order By: Relevance
“…of environmental cues that influence embryonic fate commitment to increase the rate of a given morph is well documented (Braendle et al 2006;Brisson and Stern 2006). However, our data also suggest that multiple mechanisms might be intertwined due to the fact that the fate of embryos is likely decided in the grandmother (two generations after environmental cue exposure) and the window of plasticity in the development process of A. pisum is still unknown (Dixon 1998;Brisson et al 2007) (emerging embryos are present in old embryos inside adult aphid, which inspires the term of telescopic generations; Dixon 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of environmental cues that influence embryonic fate commitment to increase the rate of a given morph is well documented (Braendle et al 2006;Brisson and Stern 2006). However, our data also suggest that multiple mechanisms might be intertwined due to the fact that the fate of embryos is likely decided in the grandmother (two generations after environmental cue exposure) and the window of plasticity in the development process of A. pisum is still unknown (Dixon 1998;Brisson et al 2007) (emerging embryos are present in old embryos inside adult aphid, which inspires the term of telescopic generations; Dixon 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover microarray analysis has revealed that photoperiodic signals regulate essentially the transcripts of cuticular proteins and kinases involved in the cascade of cellular signaling and signal transduction (Le Trionnaire et al 2007). In aphids, the control of cuticular permeability is essential to resist the stress of desiccation and to contribute to maintaining the high internal osmotic pressure generated by osmolytes, such as sugars and polyols (Kaersgaard et al 2004;Brisson and Stern 2006). We 1 Corresponding authors.…”
mentioning
confidence: 99%
“…The most abundant invertebrate genus was Acyrthosiphon, which includes the pea aphid Acyrthosiphon pisum. This genus provides a unique opportunity to test the reliability of our methodology as pea aphids require a bacterial endosymbiont, Buchnera aphidicola, for survival and reproduction (Baumann et al 1995;Brisson and Stern 2006). Thus we would expect the count of reads identified with B. aphidicola to exhibit the same pattern as that observed with A. pisum reads.…”
Section: Poisson Two-sample Textmentioning
confidence: 93%
“…Circulatory viruses contain numerous N-linked glycosylation sites on their surface cells. Many of these sites contain high-mannose glycans which could interact with mannose-binding lectin such as ConA (Gray et al, 1999;Brisson and Stern, 2006;Hogenhout et al, 2008;Desoignies, 2008;Thielens et al, 2002;Pereira et al, 2008;Naidu et al, 2004;Dimitrov, 2004;Garret et al, 1993;Wei, 2007).…”
Section: Interaction With Virus Transmissionmentioning
confidence: 99%